THE INFLUENCE OF MARXISM THOUGHT THAT ARE CONTAINED IN â€œLES JUSTESâ€ DRAMA SCRIPT BY ALBERT CAMUS - Hadiansyah Yanuar Rizqi Aktsar (Proceeding IICACS, 2019)
Karl Marx is told as an inspirator with great ideas. Marx claimed that there are laws of social development as well as the opening of secrets about a capitalist economy. Indeed at the level of theory, communism has a noble purpose but in practice many bad things happened. Lenin was the first thinker of marxism to bring marxism to actual practice, a revolution run by it to realize the utopia of Marxism in which Marxism in the hands of Lenin is not a philosophy of ordinary economics. The Just Assassins (original French title: â€•Les Justesâ€–, a more literal translation is The Just or The Righteous) is a drama script in 1949 by French writer and philosopher Albert Camus. The drama is based on the true story of a group of Russian Socialist-Revolutionaries who killed Grand Duke Sergei Alexandrovich in 1905, and explored the moral issues associated with murder and terrorism. In the drama, all but one (Stepan) of "Justes" is based on historical terrorists, described in Memoirs of a Terrorist by Boris Savinkov. This study aims to analyze the thought of an Albert Camus about a rebellion which he says is not as a form of resistance of the proletariat against the capitalist in the specific sense of Marxian or in other words that the existence of Marxism as a form of resistance to the domination of capitalism. Which prefers to human rebellion in the sense of opposing all sorts of life situations that are sickening, or in other words opposing the process of creation that has occurred by itself. With another meaning that is as a form of aspiration to obtain clarity and unity of a thought, so that in the form of a paradox, will lead to the level of form and public order. Camus believes that rebellion is one of the many essential dimensions of human nature. The Kaliayev character in this text provides a new perspective in the view of the revolution in order to bring out a political order or power existing in a society.Keywords: marxism; anarchism; karl marx; bakunin; realist theat